Asphyxia Homicides in Finland, 1983–2012 - Pia Wahlsten; Anders Eriksson (Blackwell Publishing Inc., 2022)
Finland has one of the highest homicide rates in Western Europe, and almost every tenth homicide is caused by asphyxiation. Reliable statistics, a strict legislation, and an exceptionally high medico‐legal autopsy rate formed a base for a nationwide analysis of asphyxia homicides (n = 383) during 30 years. The cases were identified through multiple records, and all the forensic pathology case files were studied in detail. In more than one out of five cases, there were indications of staging, and the homicide was revealed first at autopsy in close to one in ten cases. The vast majority of the homicides took place in private locations and involved persons known to each other. Every third victim was an intimate partner, and every tenth a child. Almost half of the victims died from manual strangulation, one in three from ligature strangulation. Smothering, choking, neck compression with a firm object, and thoracic compression were more rare methods. Drownings were excluded from this study material. Of all the victims, 7% had no observable external injuries. Petechiae were recorded in approximately in 61%, laryngohyoid fractures in 47%, and vocal cord hemorrhages in 16% of the cases. Every tenth female victim had genital injuries. Toxicological analyses were performed in close to all of the cases, and almost three out of four victims tested positive for blood alcohol. The various aspects of the demographics and autopsy findings covered in this study contribute reliable and accurate data to further strengthen the spectrum of observable medico‐legal characteristics of asphyxia homicides.